2022
DOI: 10.3390/life12010115
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiles of the Creeping Wood Sorrel Oxalis corniculata in Radioactively Contaminated Fields in Fukushima: Dose-Dependent Changes in Key Metabolites

Abstract: The biological impacts of the Fukushima nuclear accident, in 2011, on wildlife have been studied in many organisms, including the pale grass blue butterfly and its host plant, the creeping wood sorrel Oxalis corniculata. Here, we performed an LC–MS-based metabolomic analysis on leaves of this plant collected in 2018 from radioactively contaminated and control localities in Fukushima, Miyagi, and Niigata prefectures, Japan. Using 7967 peaks detected by LC–MS analysis, clustering analyses showed that nine Fukush… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 121 publications
(152 reference statements)
0
13
0
Order By: Relevance
“…This field-laboratory paradox was explained by the field effect hypothesis: the host plant in the field responded to low-level radiation stress by upregulating metabolites that were toxic to larvae as a part of plant defense mechanisms [ 59 , 67 ]. Subsequent studies have reported upregulated and downregulated metabolites and nutrients in plant leaves [ 48 , 49 , 50 ], supporting this field effect hypothesis.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…This field-laboratory paradox was explained by the field effect hypothesis: the host plant in the field responded to low-level radiation stress by upregulating metabolites that were toxic to larvae as a part of plant defense mechanisms [ 59 , 67 ]. Subsequent studies have reported upregulated and downregulated metabolites and nutrients in plant leaves [ 48 , 49 , 50 ], supporting this field effect hypothesis.…”
Section: Introductionmentioning
confidence: 60%
“…The Fukushima nuclear accident was reported to have caused various biological and ecological effects on animals, such as birds [ 31 , 32 , 33 ], insects [ 34 , 35 , 36 , 37 , 38 , 39 ], Japanese monkeys [ 40 , 41 , 42 ], and intertidal invertebrates [ 43 ], plants such as rice [ 44 , 45 ], fir trees [ 46 ], red pine trees [ 47 ], and the creeping wood sorrel Oxalis corniculata [ 48 , 49 , 50 ], and soil microbes [ 51 ]. A series of our studies [ 31 , 32 , 33 , 34 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ] demonstrated that the pale grass blue butterfly has been severely affected by the Fukushima nuclear accident.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to other lycaenid butterflies, the pale grass blue butterfly sequesters flavonoids from the host plant leaves in the wing scales [ 78 , 79 ]. Creeping wood sorrel contains pigments (such as carotenoids and flavonoids) and other secondary metabolites [ 78 , 79 , 80 , 81 , 82 ]. There is a reasonable possibility that the maternal effects detected in the present study may be caused by the deposition of flavonoid precursors in eggs by mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary metabolites were further examined in the plant collected from contaminated fields in Fukushima (Sakauchi et al, 2022). Again, stress‐related metabolites were upregulated.…”
Section: Plants and Soil Microbesmentioning
confidence: 99%